Body composition and nutritional requirements of calcium and phosphorus in growing Santa Inês lambs - Geraseev, Luciana Castro; Santos, Cristiane Leal dos; Teixeira, Júlio César; Bonagurio, Sarita; Pérez, Juan Ramón Olalquiaga (Pesquisa Agropecuaria Brasileira, 2001)
Two experiments were conducted with the objective to determine body composition and to estimate the nutritional requirements in Ca and P in growing Santa Inês lambs. In each experiment, eighteen animals were used, with 25 to 35 kg of live weight, in the first, and with 15 to 25 kg in the second experiment. Six animals were slaughtered at the beginning of each experiment to access the amount of Ca and P retained in the body, which were used as reference animals for the comparative slaughter method. Six animals were fed ad libitum and six received restricted food. The net requirements of Ca and P for empty body weight gain were estimated from derivation in the regression equations of the total mineral present in the empty body based on the empty body weight. The net requirements of Ca and P for kg of live weight (LW) gain for lambs with 15, 25, and 35 kg of LW were, respectively, 11.63, 10.52 and 9.82 g of Ca and 5.82, 4.99 and 4.28 g of P.